Minimum Wage Policy : Lessons with a Focus on the ASEAN Region - World Bank (Washington, DC, 2014)
As developing economies continue to mature and enter the next phase of reforms, labor market issues and key policy instruments such as the minimum wage increasingly come to the forefront. Increased globalization and wider competition compel countries to make labor markets more flexible so as not to hurt competitiveness. At the same time, policymakers face pressure to rethink labor market regulations (and social safety nets) to avoid disadvantaging workers, especially the most vulnerable who are more prone to employment insecurity. Evidence of the impact of minimum wage policies in the East Asian context and in Association of South East Asian Nations (ASEAN) countries, more specifically remains very limited. A thorough literature search identified only a few rigorous studies of the impact of minimum wages on important welfare outcomes in ASEAN countries, and some of the evidence was narrowly focused on one sector and period or from a time when the institutional setup and management of the policy was different from today. Given the relevance of the minimum wage policy in ASEAN economies, which are experiencing rapid economic growth accompanied by rising income inequality and persistent poverty among unskilled workers, having this evidence seems critical. The objective of this report is to contribute to the ongoing (and renewed) debate on the use of minimum wage policy as a tool for addressing various socioeconomic issues. It assumes minimum wages will remain in place, and the analysis seeks to address knowledge gaps on the policy's effects on worker outcomes and firm performance in order to provide guidance to policymakers in ASEAN countries (and similar contexts) on how to best manage the policy. This report consists of seven chapters and is divided into three parts. Part one focuses on the minimum wage policy, its historical evolution, and the current institutional context across ASEAN countries. Part two delves into the socio-economic impacts of the minimum wage policy on workers, households, firms, the economy, and the ASEAN region. Part three links the findings from each country to the ASEAN regional context and brings all the analysis together into a policy and operational discussion.